Given that, $ f(mn) = f(m) f(n) \quad \longrightarrow (1)$

And, $ f(24) = 54 $

$ \Rightarrow f (2 \ast 12) =54$

$ \Rightarrow f(2) f(12) =54$

$ \Rightarrow f(2) f(2*6) =54$

$ \Rightarrow f(2) f(2) f(6) =54$

$ \Rightarrow f(2) f(2) f(2\ast 3) = 54$

$ \Rightarrow f(2) f(2) f(2) f(3) = 54$

$ \Rightarrow \left( {f(2)} \right)^{3} f(3) = 3^{3} \times 2$

On comparing both sides, we get

$ \boxed {f(2) = 3, f(3) = 2}$

Therefore, $f(18) = f(2*9) = f(2) f(9)$

$\qquad \qquad = f(2) f(3*3) = f(2) f(3) f(3)$

$\qquad \qquad = 3\ast 2\ast 2 =12 $

Correct Answer $: 12$